(untitled) (Universal International Scientific Journal, 2026)
This analysis is based on the analysis of the dynamics of the Aridity Index (AI = P/PET) in the Kyzylkum region from 2000 to 2024. The annual variability of the AI ​​is estimated based on GPM precipitation (P) and MODIS potential evapotranspiration (PET) data, which represents the water balance and drought level of the region. Keywords: Kyzylkum, arid region, drought, climate change